Effectiveness of Semantic Feature Analysis on Naming Ability in Individuals with Aphasia in Surakarta - Ghefira Maha Ghaysa; Hafidz Triantoro; Setyadi Nugroho (e-Journal of Linguistics, 2026)
The purpose of this research was to see how the Semantic Feature Analysis (SFA) approach improved the naming skills of people with aphasia in Surakarta. Aphasia's major lexico-semantic symptom is anomia, or trouble finding words, which greatly hinders communication and quality of life. This study was designed to improve evidence-based treatment for this group. The research used a quantitative pre-experimental design with a single group pre-test and post-test. The sample consisted of ten people with aphasia, mostly Broca's type (80%), who were chosen by purposive sampling in Surakarta. The intervention, Semantic Feature Analysis, was delivered over 12 sessions. Naming ability was assessed using the TADIR instrument, and results were analyzed using a Paired T-Test. The study found a significant change in naming scores before and after the SFA intervention, with a p-value of 0.000 (≤ 0.05). This resulted in the rejection of the null hypothesis (H0), indicating that the SFA intervention is beneficial.